2009
DOI: 10.1111/j.1574-6968.2009.01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilin regulation in thepilTmutant ofNeisseria gonorrhoeaestrain MS11

Abstract: The ATPase protein PilT mediates retraction of type IV pili (Tfp). Tfp retraction of Neisseria gonorrhoeae causes many signal transduction events and changes in gene expression in infected epithelial cells. To find out whether a pilT mutation and lack of Tfp retraction, respectively, lead also to gene regulation in bacteria we performed microarrays comparing the transcriptional profiles of the N. gonorrhoeae parent strain MS11 and its isogenic pilT mutant during growth in vitro. A loss-of-function-mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…The PilC protein(s) may operate on a similar principle, allowing an N. gonorrhoeae cell to sense the resistance from neighboring cells tethered to its retracting Tfp and coordinate community and infection behavior through transcriptional reprogramming. In support of this hypothesis, the Δ pilT mutant displays a different transcriptional profile than its wt parent (38). …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The PilC protein(s) may operate on a similar principle, allowing an N. gonorrhoeae cell to sense the resistance from neighboring cells tethered to its retracting Tfp and coordinate community and infection behavior through transcriptional reprogramming. In support of this hypothesis, the Δ pilT mutant displays a different transcriptional profile than its wt parent (38). …”
Section: Discussionmentioning
confidence: 81%
“…N. gonorrhoeae pilT L201C grew as well as the wt parent in liquid (data not shown). N. gonorrhoeae Δ pilT is known to be hyperpiliated and to produce significantly higher levels of PilE and pilE mRNA than the wt (2, 38). We found that N. gonorrhoeae pilT L201C transcribed the Tfp-associated genes pilE , pilT , pilT2 , pilU , and pilF at wt levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data are consistent with observations made in other organisms, such as the cyanobacterium Synechocystis sp. strain PCC6803 and Neisseria gonorrhea, where hyperpiliated pilT mutants have been shown to accumulate higher than normal levels of pilA1 transcript (5,14). One attractive model is that as the pilus is dissembled, PilS senses pilin levels associated with the inner membrane and regulates PilR activity and pilA transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative reverse transcription-PCR (qRT-PCR), performed as previously described (34), was used to confirm microarray results and analyze expression of the tryptophanase operon, holE, hha, and ydgT. Briefly, 1 g of total RNA was reverse transcribed to generate cDNA using the high-capacity cDNA reverse transcription kit (Applied Biosystems) as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%